Adverse drug reactions due to drug- drug interactions with proton pump inhibitors: assessment of systematic reviews with AMSTAR method - OKUYAN, BETÜL; SANCAR, MESUT (TAYLOR & FRANCIS LTD, 2016)
Introduction: Many systematic reviews resulted in claims on drug-drug interactions (DDIs) with proton pump inhibitors (PPIs). Such a large number begs for consensus on the clinical significance of findings.Areas covered: We critically evaluated the safety of PPI use with respect to DDIs with a meta-review of systematic reviews published between 1978 and 2015. We assessed the evidence by their reliability, repeatability, transparency, and objectivity according to the Assessment of Multiple Systematic Reviews (AMSTAR) criteria.Expert opinion: Clinicians must assess risks for each PPI for certain comorbid conditions. DDIs don't substantiate class effect for PPIs; each PPI could induce unique DDIs. Concomitant use of PPIs with thienopyridines (e.g. clopidogrel) could be justified in patients without strong affinity to cytochrome CYP2C19 and with high risk of bleeding (e.g. patients with prior upper gastrointestinal bleeding, Helicobacter pylori infection, advanced age, steroid treatment, and nonsteroidal anti-inflammatory drug use). DDIs could occur in an AIDS subpopulation treated with highly active antiretroviral therapy (HAART). DDIs exist for cancer patients undergoing targeted therapy. Hypomagnesemia could increase in the setting of advanced age and polypharmacy. Omeprazole poses high risks owing to its pharmacokinetic DDI profile. Future systematic reviews should incorporate these additional risks for better clinical guidance
Keywords: Adverse drug reactions; Assessment of Multiple Systematic Reviews; drug-drug interactions; proton pump inhibitors; meta-review; systematic review; AMSTAR; PPI; DDI; ADR; PATIENTS RECEIVING CLOPIDOGREL; COATED MYCOPHENOLATE SODIUM; METHODOLOGICAL QUALITY; METFORMIN PHARMACOKINETICS; POTENTIAL INTERACTIONS; INTERACTION PROFILES; MEASUREMENT TOOL; ACID; LANSOPRAZOLE; OMEPRAZOLE